Report of the Premier African Organisation for Research and Training in Cancer Virtual Genomics Conference held from 18–20 February 2021 - Ayettey, Hannah; Fernandez, Pedro; Rodrigues, Belmira (ecancer, 2021)
The rapidly rising cancer burden and mortality rate in Africa are in contrast to the increase in cancer survivorship in Europe and North America. Genomic medicine has contributed to the rise in survival and has facilitated precision cancer control. However, there is a shortage of African representation in genomic databases, even for cancers that disproportionately affect Africans. To improve this outlook and address research in genomics and genetics relevant to Africa and people of African descent, the African Organisation for Research and Training in Cancer (AORTIC), under the Research Committee’s auspices, organised the Cancer Genomic Conference. The conference aimed to develop a roadmap for cancer genomics research to control the continent’s increasing cancer burden. Presentations at the conference revealed that: (1) Africa is made up of a highly heterogeneous group of people with diverse ethnic groups, (2) Very few African countries have been the focus of cancer genomics research, (3) Cancer exacts a heavy burden on global populations across the African diaspora with obvious genetic variants and cancer disparities and (4) There are differences in the contribution of genetics by race or ancestry and these differences are likely due to evolutionary genetics, contextual factors and genomic architecture. The importance of data security, ethics and integrity of the African genomics data was emphasised. The implementation of the conference highlights will provide the bedrock for pharmacogenomics to guide treatment decisions for cancer in Africa. The conference concluded with the formation of an AORTIC Special Interest Group on cancer genomics. It is the goal of this group to drive the implementation of this Conference’s outcomes.
Keywords: Africa; African Organization for Research and Training in Cancer (AORTIC); cancer; genomics; ACE: Applied Informatics and Communication; CAPiC; Covenant University; Belmira Rodrigues; Omolara Aminat Fatiregun